2017
DOI: 10.28945/3905
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of ERP Systems: The Uses and Gratifications Theory Perspective

Abstract: Aim/PurposeThis study aims to provide a better understanding of individual acceptance of enterprise resource (ERP) systems. Based on the uses and gratifications theory (UGT) and informing science theory, the study developed and empirically tested a research model to explain the effects of ERP characteristics (specifically, informativeness and enjoyment) on ERP acceptance and use. Background Individual acceptance of ERP systems is crucial for achieving the benefits associated with ERP systems. Unfortunately, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…These results support the information science theory, which states that information provided by the system to help users work effectively determines the user acceptance of the system. Moreover, research results have shown that the enjoyment of the ERP system has a great effect on users' satisfaction with and attitude toward the system (Hasan, 2017).…”
Section: Delone and Mclean (Dandm) Is Success Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…These results support the information science theory, which states that information provided by the system to help users work effectively determines the user acceptance of the system. Moreover, research results have shown that the enjoyment of the ERP system has a great effect on users' satisfaction with and attitude toward the system (Hasan, 2017).…”
Section: Delone and Mclean (Dandm) Is Success Modelmentioning
confidence: 99%
“…A research was carried out by Hasan (2017) at the University of Toledo, USA, where a different model was used to study ERP system users' acceptance. According to Hasan, most studies in the context of ERP system use and acceptance used TAM, which focuses mainly on the behavioral part of users' acceptance and use of the ERP system.…”
Section: Table 1 Continuedmentioning
confidence: 99%